Дослідження Шацького городища на Волині у 2009 році - Златогорський, Олексій Євгенович; Демедюк Сергій; Zlatohorskyi, Oleksii Ye.; Demediuk Serhii (My University, 2010)
У статті проаналізовано результати досліджень городища у селищі Шацьк у 2009 р.: на площі 188 кв.м. виявлено і досліджено 14 археологічних об'єктів

The grad situated in the place Śac'k occupies the high promontory by Lake Lûcimir. In year 2009 it was excavated 188 m2 of the area discovering 14 objects (12 cottages and 2 farm pits). Single artefacts (fragments of pottery, coins, and ornaments) should be related to the first centuries Anno Domini, however most of materials came from 10th–12th and 13th–14th cent. They include artefacts made of clay, glass and bone, elements of the armament, coins, ornaments made of precious metals, and market seals indicating that the excavated grad was an important trading centre in this period identified with the well-known from chronicles „the Paradise city”.
The research carried out in 2009 in the in the grad Śac'k on Volyn
Keywords: Волинь; Шацьк; Люцимир; Рай; городище; Śac'k; Volyn; Ukraine; excavation; grad; trading centre; “the Paradise city”